Fabrication of silver nanoparticles by laser ablation technique: their characterization and uses - Haider, A F M Yusuf; Talukder, Aminul I. (© 2013 Nova Science Publishers, 2017)
This book chapter was published in the book Silver Nanoparticles: Synthesis, Uses and Health Concerns [© 2013 Nova Science Publishers, Inc.] and the definite version is available at: https://www.novapublishers.com/catalog/product_info.php?products_id=45615